Isoflurane sedation in patients undergoing VA-ECMO treatment for cardiogenic shock – an observational propensity-matched study. (25th November 2020) - Scherer, C; Kupka, D; Stocker, T; Joskowiak, D; Scheuplein, H; Schoenegger, C; Stremmel, C; Luesebrink, E; Stark, K; Orban, M; Peterss, S; Hausleiter, J; et al.
Abstract: Introduction: The feasibility and hemodynamic effects of isoflurane sedation in cardiogenic shock in the presence of extracorporeal membrane oxygenation (VA-ECMO) treatment is currently unknown. Methods: Thirty-two cardiogenic shock patients with VA-ECMO treatment under sedation with volatile isoflurane on a cardiac intensive care unit have been enrolled in this retrospective single-center study and were matched by propensity score in a 1:1 ratio with intravenously (IV) sedated patients. Results: Administration of isoflurane was associated with lower IV sedative drug use during VA-ECMO treatment (86% vs. 32%, p=0.01). Mean systolic arterial pressure was similar (94.3±12.6 mmHg versus 92.9±10.5 mmHg, p=0.65), but mean heart rate was significantly higher in the conventional sedation group, when compared to the isoflurane group (85.2±20.5 / min vs. 74.7±15.0 /min; p=0.02). Catecholamine doses, VA-ECMO blood and gas flow, ventilation time (304±143 h vs. 398±272 h, p=0.16), bleeding complications BARC3a or higher (59.3% vs. 65.3%, p=0.76) and 30-day mortality (59.2% vs. 63.4%, p=0.80) were similar in both groups. Conclusions: Volatile sedation with isoflurane is feasible in patients with cardiogenic shock and VA-ECMO treatment and was not associated with higher catecholamine dosage or ECMO flow rate compared to IV sedation. Funding Acknowledgement: Type of funding source: None